Visuospatial Changes after Clipping of Anterior Communicating Artery Aneurysms - Cechi, Camila Santos; Oliveira, Leonardo B.; Martin, Ibero Ramazini; Micieli, Ana Paula; Vismara, Jessica de Oliveira D.; Silva, Guilherme Melo; Batista, Sávio; Bertani, Raphael; Pedroso, Cristiano; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Introduction A series of symptoms are commonly seen after anterior communicating artery (ACoA) aneurysm clipping. Previous studies designated it as ACoA syndrome, a condition in which symptoms like amnesia, confabulation, and personality changes are observed. The present study investigates visuospatial impairments associated with ACoA aneurysm rupture followed by subarachnoid hemorrhage (SAH) and clipping procedure.Methods 31 patients who underwent surgical clipping of the ACoA after SAH were evaluated prospectively at three, six, and twelve months after the surgery. Hooper Visual Organization test (HVOT), Judgment of Line Orientation test (JLOT), and Stroop-I test were used to evaluate visual organization, visual orientation perception, and visual attention, respectively.Results Regarding the HVOT, the mean score observed in each observation was at three, six, and twelve months, respectively: 20.2 (SD ± 4.4), 21.5 (SD ± 4.7), and 20.9 (SD ± 4.6). The JLOT, in turn, presented the following results at the same respective time frames: 19.0 (SD ± 4.9); 19.7 (SD ± 4.3); 21.2 (SD ± 4.7). Finally, for the Stroop-I test, a similar pattern was found: 18.35 (SD ± 5.8); 18.00 (SD ± 6); 17.00 (SD ± 4.4). Of all the tests above, only Stroop-I test scores did not follow a normal distribution.Conclusion Visuospatial and visuoperceptual abilities can also present impairments after SAH following ACoA aneurysm rupture and clipping, although it is commonly a mild symptom. Therefore, diffuse symptomatology, rather than the stricter ACoA syndrome described in the literature, may be seen. Moreover, positive outcomes are expected twelve months after postoperatively.
Keywords: subarachnoid hemorrhage; anterior communicating artery; intracranial aneurysm; visuospatial changes; visuospatial abilities; visual impairment